Associations among milk production and rectal temperature on pregnancy maintenance in lactating recipient dairy cows - Vasconcelos, José Luiz Moraes [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Jardina, D. T. G. [UNESP]; Aragon, F. L.; Veras, M. B.; Soriano, S.; Sobreira, N.; Scarpa, A. B. [UNESP] (Elsevier B.V., 2011)
The objective of this study was to evaluate the associations among milk production, rectal temperature, and pregnancy maintenance in lactating recipient dairy cows. Data were collected during an 11-mo period from 463 Holstein cows (203 primiparous and 260 multiparous) assigned to a fixed-time embryo transfer (ET) protocol. Only cows detected with a visible corpus luteum immediately prior to ET were used. Rectal temperatures were collected from all cows on the same day of ET. Milk production at ET was calculated by averaging individual daily milk production during the 7 d preceding ET. Pregnancy diagnosis was performed by transrectal ultrasonography 21 d after ET. Cows were ranked and assigned to groups according to median milk production (median = 35 kg/d; HPROD = above median; LPROD = below median) and rectal temperature (<= 39.0 degrees C = LTEMP; >39.0 degrees C = HTEMP). A milk production x temperature group interaction was detected (P = 0.04) for pregnancy analysis because HTEMP cows ranked as LPROD were 3.1 time more likely to maintain pregnancy compared with HTEMP cows ranked as HPROD (P = 0.03). Milk production did not affect (P = 0.55) odds of pregnancy maintenance within LTEMP cows, however, and no differences in odds of pregnancy maintenance were detected between HTEMP and LTEMP within milk production groups (P > 0.11). Within HTEMP cows, increased milk production decreased the probability of pregnancy maintenance linearly, whereas within LTEMP cows, increased milk production increased the probability of pregnancy maintenance linearly. Within HPROD, increased rectal temperature decreased the probability of pregnancy maintenance linearly, whereas within LPROD cows, no associations between rectal temperatures and probability of cows to maintain pregnancy were detected. In summary, high-producing dairy cows with rectal temperatures below 39.0 degrees C did not experience reduced pregnancy maintenance to ET compared to cohorts with reduced milk production. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dairy cows; Embryo transfer; Heat stress; Milk production; Pregnancy maintenance; Rectal temperature